Urban Area Administration (Journal of Planner and Development, 2007)
As known, all urban areas are submitted to supervision of independent administration and agencies taken the responsibility of full-filling the service function and protecting the environment with limited investment allocated , controlled by several laws and arrangements, that are contradictory to each other , the result , deteriorate the level of provided services in urban areas and different environmental problems apper , In addition to waste of efforts and resources , This required a great interest to urban areas administration . So , this paper gives attention to the basic standards that must take in consideration of urban areas administration , and the constraint that faces the administration agencies in general , to achieve the treatment that improve administration performance efficiency for responsible agency of urban areas , to ensure , optimal employees for available recourses , to each best environmental and living conditions in urban areas